2012
DOI: 10.1111/j.1600-0528.2012.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index (BMI) and dental caries in 5‐year‐old children from southern Sweden

Abstract: Children with low BMI may be at risk of caries development. Low BMI may be associated with eating habits endangering dental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 16 publications
8
55
1
11
Order By: Relevance
“…This result were similar to the study done by Olivera et al, 13 Norberg et al, 2 Bahuguna et al, 11 Cameron et at, 14 and Benzian et al 15 This can be attributed to the fact that if a child is a fussy eater and underweight, parents may coerce the child to eat or offer tempting food high in carbohydrates to make sure that the child eats thus increasing risk of dental caries.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This result were similar to the study done by Olivera et al, 13 Norberg et al, 2 Bahuguna et al, 11 Cameron et at, 14 and Benzian et al 15 This can be attributed to the fact that if a child is a fussy eater and underweight, parents may coerce the child to eat or offer tempting food high in carbohydrates to make sure that the child eats thus increasing risk of dental caries.…”
Section: Discussionsupporting
confidence: 79%
“…Height was measured to the nearest 0.1 cm using a stadiometer. For calculation of BMI the following formula was used: -Weight in kg/ (height in meters) 2 . The children were then classified into four categories using age and gender specific criteria recommended by Center for disease Control and prevention.…”
Section: Tools For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…En Colombia se han reportado cifras variables, llegando a afectar más de tres cuartas partes de los niños y niñas evaluados en algunos de estos estudios [4][5][6][7], con diferentes niveles de severidad. Este problema de salud bucal es motivo de preocupación, por cuanto se tiene evidencia de que compromete el bienestar, la calidad de vida y el adecuado crecimiento y desarrollo de niños y niñas [8][9][10][11][12][13].…”
Section: Introductionunclassified
“…This linear inverse relationship was found in an Australian longitudinal study 27 . Furthermore, a Swedish study 28 showed the relationship between different categories of BMI and untreated caries. This unavoidable relationship is confounded by a lot of conditions.…”
Section: Discussionmentioning
confidence: 99%